2007
DOI: 10.4049/jimmunol.179.7.4808
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for TLR4 in the Pathogenesis of Necrotizing Enterocolitis by Modulating Intestinal Injury and Repair

Abstract: Necrotizing enterocolitis (NEC) is the leading cause of death from gastrointestinal disease in preterm infants and is characterized by translocation of LPS across the inflamed intestine. We hypothesized that the LPS receptor (TLR4) plays a critical role in NEC development, and we sought to determine the mechanisms involved. We now demonstrate that NEC in mice and humans is associated with increased expression of TLR4 in the intestinal mucosa and that physiological stressors associated with NEC development, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
518
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 422 publications
(547 citation statements)
references
References 90 publications
28
518
1
Order By: Relevance
“…After prolonged exposure to LPS, as was observed in a model of chronic murine endotoxemia in experimental NEC, the expression of CD14 within the intestinal mucosa is decreased. Given recent findings from our laboratory and the Caplan laboratory demonstrating the importance of LPS-mediated signaling in the pathogenesis of NEC (9,10), we now propose a novel role for CD14 in the regulation of LPS signaling, potentially contributing to the initiating events in the development of NEC.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…After prolonged exposure to LPS, as was observed in a model of chronic murine endotoxemia in experimental NEC, the expression of CD14 within the intestinal mucosa is decreased. Given recent findings from our laboratory and the Caplan laboratory demonstrating the importance of LPS-mediated signaling in the pathogenesis of NEC (9,10), we now propose a novel role for CD14 in the regulation of LPS signaling, potentially contributing to the initiating events in the development of NEC.…”
Section: Discussionmentioning
confidence: 87%
“…Our group and the group of Caplan and colleagues have recently shown that TLR4 plays a key role in the development of experimental NEC in vivo, as animals with mutations in TLR4 were found to be protected from the development of this disease as compared to wild-type counterparts (9,10). We have shown that the role of TLR4 in the pathogenesis of NEC involves an exacerbation of enterocyte injury and an inhibition of mucosal repair mechanisms (9). Expression of TLR4 was also found to be increased in the early stages of NEC (9,10).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…An evidence for such defective repair mechanisms was found when the role of TLR4 was evaluated in a neonatal murine model of NEC. It was found that in experimental NEC, in addition to increased apoptosis as was shown earlier, there was a reduced epithelial cell proliferation and defective migration along the crypt villus axis; these defects required intact TLR4 signaling and were accompanied with an increased phosphorylation of focal adhesion kinase (FAK) on S722, i.e., a phosphorylation state of FAK that inhibits epithelial cell migration [82]. In vitro, TLR4 activation resulted in FAK phosphorylation and inhibited enterocyte migration.…”
Section: The Role Of Defective Repair Mechanisms In Necmentioning
confidence: 76%
“…Additionally, we have shown that PAF does not only directly regulate apoptosis, but that signaling via the PAFR induces TLR4 expression in enterocytes (unpublished data). TLR4, the receptor for LPS, has been shown to take part in NEC pathogenesis [73,82], causes enterocyte apoptosis [101] and defective enterocyte migration [82]. Furthermore, TLR4 activation leads to induction of inflammatory molecules such as TNFα [102] and nitric oxide (NO) [103]; both of these molecules have been shown to be involved in NEC pathogenesis [15,81,104] and have been shown to be pro-apoptotic for enterocytes [81,105].…”
Section: Pro-apoptotic Signaling In Necmentioning
confidence: 99%